Unveiling the Re segregation at γ/γ′ interface in Ni-based superalloy. (November 2021) - Zhang, Jiachen; Huang, Taiwen; Lu, Fan; Cao, Kaili; Wang, Dong; Zhang, Jian; Zhang, Jun; Su, HaiJun; Liu, Lin
Abstract: The distribution of Re in a Ni-based single crystal superalloy is specified by atom probe tomography after different heat treatment. At higher temperatures (950-1100°C), the Re diffusivity in γ matrix is becoming smaller than the actual effective diffusion for γ΄ growth, during the subsequent cooling process and the interface migration, consequently Re atoms are insufficient to diffuse away and keep accumulating, leading to forming segregation at γ/γ′ interface. While at low temperatures (800-900°C), the Re diffusion is capable of balancing the effective diffusion for γ΄ growth. After introducing more alloys with different Re content and different aging temperatures, Re segregation is irrelevant to the Re content but highly temperature-dependent. These results provide a novel perspective on the comprehension of the Re effect on γ΄ growth in Ni-based superalloy and are valuable to both improving the γ/γ′ microstructure stability and designing high-performance superalloys.